MODIFICATION OF THE NDOSEQ CODE IN THE LIGHT OF ICRP-60 RECOMMENDATIONS - Ashfaq, A.; Ullah, Mati; Ullah, Mati (The Nucleus, 2020)
After the availability of additional data, the International Commission on Radiological Protection (ICRP) revised the Quality Factors for neutrons and instead has recommended radiation weighting factors (WR) in their Report No. ICRP-60. These recommendations have serious consequences for many operational neutron dosimetry services. The ICRP-60 recommendations include the reduction in dose limits from 50 mSv to 20 mSv per year, change in the quality factors and the dose estimation in some circumstances down to a few mSv per year. The overall effect of the ICRP-60 recommendations is to reduce the detection threshold in order to account for the reduction in the effective equivalent dose. We have studied the impact of ICRP-60 recommendations on the response of CR-39 based fast neutron dosimeter and have modified the computer code NDOSEQ in the light of ICRP 60 recommendations. The NDOSEQ Code simulates the dose equivalent response of the electrochemically etched CR-39 detector to fast neutron in the energy range of 70 keV to 20 MeV for up to five hydrogenous front radiators.